The market regulation triad: Antitrust, industrial policy and protectionism in the optical fiber market - Andrey E. Shastitko (Ural State University of Economics, 2021)
Implementation of the import substitution strategy in Russia in some cases is associated with the risk of the state supporting technologically ineffective domestic producers, whose interests are taken into account in the course of industry regulation and antitrust. The article examines the problems of using the tools of antimonopoly policy (and its relationship with industrial policy) in the context of launching single-mode optical fiber by a Russian company with limited technological production competencies in the short term. While analyzing the results of optical fiber antitrust case, the authors identify the distortion of the Russian competition policy objectives and the misuse of its tools. Methodologically, the study rests on industrial organization theory, antitrust economics and new institutional economic theory (in particular, institutional design). Data from the analytical agency CRU Monitor and customs statistics are used as the information base for quantitative (economic-statistical) analysis. The article identifies the factors that determine the dynamics of the optical fiber market: demand for optical fiber cable (product of the related market); production capacities of preforms as the main raw material for optical fiber; integration of the stages of the optical fiber production process; and investments in R&D. The Elzinga-Hogarty test was performed to delimit the geographical boundaries of the single-mode fiber market. The results shows that the Federal Antimonopoly Service of Russia drew false conclusions about narrow geographical boundaries within the Russian Federation. This conclusion is important in terms of complying with the procedure for analyzing the competition in commodity markets, since incorrect delimitation of the market’s geographical boundaries can lead to erroneous estimates of market concentration and the mistaken detection of a company’s market dominance as a potential competitor of a domestic manufacturer. Lobbying the interests of national manufacturers not only contradicts the principles of competition protection, but also reduces the incentives of new market players to innovate and accumulate knowledge specific to the industry, which is one of the key factors of competitiveness in the optical communication markets.